Konvergensi Media Pare Pos Di Era Digital - Siska, Siska Pratiwi (Journal of Media and Communication Studies, 2024)
Technological developments that are increasingly accelerating at this time will certainly make people get carried away with its development, like it or not, people will continue to use it. One of the technological developments is the presence of new media or new media. Through convergence it becomes a challenge for the newspaper print media industry to meet the needs of its readers. The content of the news is designed in a more creative way that attracts readers. Print media must also make updates by utilizing technology such as creating platforms, namely e-papers that can be accessed through online media so that the existence of print media can survive with the help of existing technology. The purpose of this study is to find out how the form of media convergence is carried out by Pare Pos? To find out how the survival strategy through Pare Pos media convergence through alternative media? The theory used by researchers is the Media Convergence Theory and Media Ecology Theory. Convergence is a radical change in the handling, supply, distribution and processing of all forms of information both visual and audio, data and so on. The type of research used by researchers is a type of qualitative research, which is a research approach that uncovers certain social situations by describing reality correctly, formed by words based on techniques of collecting and analyzing relevant data obtained from natural situations. The forms of media convergence carried out by Pare Pos are newsrooms, multitasking and multiplatform so as not to be left behind in technological developments in all-digitalization while the convergence strategy carried out by Pare Pos consists of multimedia, multichannel and multiplatform.